Toward Understanding Gift-Giving in Relationships - Mann, David P. (Missiology, 1990)
As the subject of stewardship is taught in a church where Western missionaries work in close collaboration with African church leaders, intercultural friction is inevitable. One culture stresses interconnectedness and sharing; the other emphasizes independence and self-sufficiency. But both see wealth as a primary means of expressing those values. This article reviews aspects of economic anthropology which relate to gift-giving, analyzes parts of the Dowayo culture, and draws missiological conclusions. Understanding the economic assumptions of a culture can inform biblical teaching on Christian stewardship and aid its integration into the life of the church.